The Diffused Vortex Hydrodynamics Method (Communications in Computational Physics, 2018)
A new Particle Vortex Method, called Diffused Vortex Hydrodynamics(DVH), is presented in this paper. The DVH is a meshless method characterized by theuse of a regular distribution of points close to a solid surface to perform the vorticitydiffusion process in the boundary layer regions. This redistribution avoids excessiveclustering or rarefaction of the vortex particles providing robustness and high accuracyto the method. The generation of the regular distribution of points is performedthrough a packing algorithm which is embedded in the solver. The packing algorithmcollocates points regularly around body of arbitrary shape allowing an exact enforcementon the solid surfaces of the no-slip boundary condition. The present methodis tested and validated on different problems of increasing complexities up to flowswith Reynolds number equal to 100,000 (without using any subgrid-scale turbulencemodel).